The Relationship between Pupillometric Values and Visual Evoked Potential Test Results in Patients with Early Glaucoma - Işik, Mehmed Uğur; Şahin, Ömer Faruk (Ovid Technologies (Wolters Kluwer Health), 2020)
SIGNIFICANCEMeasuring pupil diameter may provide an additional objective method to detect and monitor glaucoma.PURPOSEThe purposes of this study were to evaluate whether pupillometry can be used in the assessment of glaucomatous damage and to determine whether pupillometer can be used in glaucoma screening.METHODSIn this retrospective study, patients with early stages of glaucomatous optic neuropathy were tested using visual evoked potential (VEP), standard automated perimetry, and pupillometer. The VEP record was made using two consecutive check sizes (1° and 15′) at 1-Hz frequency. Patients with a mean deviation of <−2 and >−6 dB were included in the study. Pupil size measurements were performed under photopic conditions at 60-, 100-, and 130-cd/m2luminance levels with the OPD Scan (Nidek, Gamagori, Japan) device.RESULTSIn all, 24 eyes of 24 patients (14 women and 10 men) with newly diagnosed open-angle glaucoma were included, and 30 eyes of 30 healthy subjects (15 women, 15 men) were used as controls. There was no significant difference between sexes in photopic pupil diameters in either group. Comparing the pupil diameters in different luminance levels, the diameters were significantly larger in the patient group. When age-corrected values in the glaucoma group were compared with an age-matched control group, the differences in P100 latency and amplitudes were statistically significant. There were significant correlations between photopic pupil diameters and timing of VEP waveforms.CONCLUSIONSThere is a relationship between pupil diameters and VEP results in eyes with early glaucoma.
Keywords: Male; Pupil; Diagnostic Techniques, Ophthalmological; Middle Aged; Evoked Potentials, Visual; Humans; Visual Field Tests; Female; Visual Fields; Glaucoma, Open-Angle; Aged; Retrospective Studies